Corrigendum: A relativistic theory of the field II - Valenzuela, Mississippi (2022)
In writing out the equations in section of Hamilton principle in my recent paper [1], inadvertents errors led to errant numerical expressions in “Field equations”. The main results and conclusions of my paper remain unchanged. All of the affected formulas are corrected below.